Samsung: Customer Loyalty Strategy in Malaysia and Colombia - Evelyn Henao Ruiz; Camilo Alberto Pérez Restrepo; Carolina Ardila Lopez; Kalaaivahnny A/P Jegathesan; Daisy Mui Hung Kee; Kamalaswari A/P Ganasan; Kalaaiveyhny A/P Jegathesan; Prasanthiney A/P Nageswara Rao (AIBPM Publisher, 2020)
Brand loyalty is one of the key elements of success in any organization, in the context of high international competition and consumer awareness. The objective of this research is to study the factors that affect customer’s loyalty towards Samsung over the long term and propose certain strategies to increase loyalty in Malaysia and Colombia. First, the company’s background is explained, followed by the research problem and the research method. By comparing these two markets, possible loyalty approaches that could be useful for each market were identified, taking into account that Samsung is the leading company in both countries, in terms of market share. Finally, concluding with the findings and limitations of the research.